Nutrient intakes in an Italian population of infants during the complementary feeding period. - Concina, Federica; Pani, Paola; Bravo, Giulia; Barbone, Fabio; Carletti, Claudia V; Knowles, Alessandra; Ronfani, Luca; Parpinel, Maria (Public Health Nutr, 2018)
OBJECTIVE: To describe the nutrient intakes of an Italian cohort of infants at 6, 9 and 12 months of age. DESIGN: Dietary data were collected using a food diary at three follow-ups (6, 9 and 12 months of age of infants). The infants' dietary data were used to estimate nutrient intakes using the Italian food composition database integrated with data from nutritional labels and the literature. The mean and standard deviation, median and interquartile range, minimum and maximum, and 5th, 25th, 75th and 95th percentiles were calculated for the daily intake of twenty-eight nutrients, with sex differences evaluated using parametric/non-parametric statistical methods. SETTING: A prospective population-based birth cohort.SubjectInfants (n 400) living in the urban area of Trieste (Italy). RESULTS: The sex distribution was fairly balanced at each follow-up. The mean daily intakes of energy and the other twenty-seven nutrients considered were greater in males at all follow-ups. In particular, a significant statistical difference was observed in higher male consumption of cholesterol at 9 months and in energy and carbohydrate intakes at 12 months (P < 0·05). The mean daily intake of proteins was greater than that recommended by the Italian Dietary Reference Values at all follow-ups. CONCLUSIONS: These preliminary results provide a useful basis for understanding the nutrient intake patterns of infants in this area of Italy during the first year of life.

Introduction of Complementary Foods in a Cohort of Infants in Northeast Italy: Do Parents Comply with WHO Recommendations? - Carletti, Claudia; Pani, Paola; Monasta, Lorenzo; Knowles, Alessandra; Cattaneo, Adriano (Nutrients, 2017)
Timing and type of complementary food in infancy affect nutritional status and health later in life. The objective of this paper was to assess complementary feeding practices, looking at timing, type, and compliance with World Health Organization (WHO) recommendations. Data were obtained from a birth cohort of 400 infants, enrolled in Trieste (Italy) between July 2007 and July 2008 and followed up for three years, using a "food introduction timing table". Five WHO recommendations standards were used to assess parental compliance and associated factors. Thirty seven percent of mothers returned the completed "timing table" up until the child was three years of age. Eighty six percent of infants were already receiving complementary foods at six months. The first food type to be introduced was fresh fruit (170 days from birth, median). Overall, infants shared a very similar diet, which was different from the family diet and characterized by delayed introduction of certain food types. Five percent of parents complied with either all five or only one of the WHO recommendations, 34% with three, and 35% with four. The parents' partial compliance with WHO recommendations is probably due to conflicting information received from different sources. This advocates for national evidence-based guidelines, supported and promoted by health professionals.
Keywords: Adult; Cohort Studies; Dairy Products; Diet; Edible Grain; Female; Follow-Up Studies; Fruit; Humans; Infant; Infant Nutritional Physiological Phenomena; Italy; Logistic Models; Male; Mothers; Patient Compliance; Recommended Dietary Allowances; Socioeconomic Factors; Vegetables; World Health Organization

Letter to the editor: Outbreak of a new measles B3 variant in the Roma/Sinti population with transmission in the nosocomial setting, Italy, November 2015 to April 2016. - Monasta, Lorenzo; Knowles, Alessandra (Euro Surveill, 2016)

Putative modifier genes in mevalonate kinase deficiency. - Marcuzzi, Annalisa; Vozzi, Diego; Girardelli, Martina; Tricarico, Paola Maura; Knowles, Alessandra; Crovella, Sergio; Vuch, Josef; Tommasini, Alberto; Piscianz, Elisa; Bianco, Anna Monica (Mol Med Rep, 2016)
Mevalonate kinase deficiency (MKD) is an autosomal recessive auto‑inflammatory disease, caused by impairment of the mevalonate pathway. Although the molecular mechanism remains to be elucidated, there is clinical evidence suggesting that other regulatory genes may be involved in determining the phenotype. The identification of novel target genes may explain non‑homogeneous genotype‑phenotype correlations, and provide evidence in support of the hypothesis that novel regulatory genes predispose or amplify deregulation of the mevalonate pathway in this orphan disease. In the present study, DNA samples were obtained from five patients with MKD, which were then analyzed using whole exome sequencing. A missense variation in the PEX11γ gene was observed in homozygosis in P2, possibly correlating with visual blurring. The UNG rare gene variant was detected in homozygosis in P5, without correlating with a specific clinical phenotype. A number of other variants were found in the five analyzed DNA samples from the MKD patients, however no correlation with the phenotype was established. The results of the presents study suggested that further analysis, using next generation sequencing approaches, is required on a larger sample size of patients with MKD, who share the same MVK mutations and exhibit 'extreme' clinical phenotypes. As MVK mutations may be associated with MKD, the identification of specific modifier genes may assist in providing an earlier diagnosis.

Advertisements of follow-on formula and their perception by pregnant women and mothers in Italy. - Cattaneo, Adriano; Pani, Paola; Carletti, Claudia; Guidetti, Margherita; Mutti, Valentina; Guidetti, Cecilia; Knowles, Alessandra (Arch Dis Child, 2015)
OBJECTIVE: To assess how follow-on formula milks for infants aged 6-12 months are presented to and understood by mothers. DESIGN: A quantitative and qualitative cross-sectional study including (1) an analysis of advertisements in three magazines for parents; (2) in-depth semistructured qualitative interviews to pregnant women on their perception of two advertisements for follow-on formula and (3) self-administered questionnaires for mothers to explore their exposure to and perception of formula advertisements. PARTICIPANTS: Eighty pregnant women 32-36 weeks of gestation with no previous children and 562 mothers of children <3 years old. SETTING: Maternal and child health centres in eight cities of Italy. RESULTS: Advertisements of formula (n=89) represented about 7% of all advertisements in the three magazines, the majority (58%) being for follow-on formula. Advertisements were parent-oriented, aimed at helping parents solve health problems of their babies or at eliciting good feelings, or both. The qualitative interviews to pregnant women showed inability to define the advertised products at first glance due to the ambiguity of the numeral 2 and the presumed age of the portrayed baby; this inability did not disappear after carefully viewing the advertisements and reading the text. When asked in the self-administered questionnaires whether they had ever come across advertisements of infant formula, 81% of mothers reported that they had, despite the legal inexistence of such advertisements, and 65% thought that it was for a product to be used from birth. CONCLUSIONS: Advertisements of follow-on formula are perceived by pregnant women and mothers as promoting infant formula.
Keywords: Adult; Advertising as Topic; Attitude to Health; Cross-Sectional Studies; Female; Humans; Infant; Infant Formula; Italy; Mothers; Perception; Periodicals as Topic; Pregnancy; Pregnant Women; Reading; Surveys and Questionnaires; Young Adult

Alendronate, a double-edged sword acting in the mevalonate pathway. - Tricarico, Paola Maura; Girardelli, Martina; Kleiner, Giulio; Knowles, Alessandra; Valencic, Erica; Crovella, Sergio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Aminobisphosphonate aledronate is a compound commonly used clinically for the treatment of osteoporosis and other bone diseases, as a result of it preventing bone resorption. However, in previous years it has also been used to obtain cellular and animal models of a rare genetic disorder termed Mevalonate Kinase Deficiency (MKD). MKD is caused by mutations affecting the mevalonate kinase enzyme, in the cholesterol pathway and alendronate can be used to biochemically mimic the genetic defect as it inhibits farnesyl pyrophosphate synthase in the same pathway. Despite evidence in favor of the inhibition exerted on the mevalonate pathway, there is at least one clinical case of MKD in which alendronate improved not only skeletal and bone fractures, as expected, but also MKD clinical features. Based on this finding, the present study assessed the anti‑inflammatory properties of this aminobisphosphonate in vitro. No anti‑inflammatory effects of alendronate were observed in the in vitro experiments. Since MKD lacks specific treatments, these results may assist scientists and physicians in making the decision as to the most suitable choice of therapeutic compounds for this neglected disease.

Comment on: 'Anthropometric parameters in relation to glycaemic status and lipid profile in a multi-ethnic sample in Italy' by Gualdi-Russo et al. - Monasta, Lorenzo; Knowles, Alessandra (Public Health Nutr, 2015)

Two‑gene mutation in a single patient: Biochemical and functional analysis for a correct interpretation of exome results. - Bianco, Anna Monica; Faletra, Flavio; Vozzi, Diego; Girardelli, Martina; Knowles, Alessandra; Tommasini, Alberto; Zauli, Giorgio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Next-generation sequencing (NGS) has generated a large amount of sequence data with the requirement of frequent critical revisions of reported mutations. This innovative tool has proved to be effective in detecting pathogenic mutations; however, it requires a certain degree of experience to identify incidental findings. In the present study, whole exome sequencing analysis was performed for the molecular diagnosis and correct genotype/phenotype correlation between parents and a patient presenting with an atypical phenotype. In addition, mevalonic acid quantification and frequency analysis of detected variants in public databases and X‑chromosome inactivation (XCI) studies on the patient's mother were performed. V377I as well as the S135L mutations were identified on the mevalonate kinase deficiency gene and the levels of mevalonic acid in the patient were 5,496 µg/ml. A D59G variation, reported in ESP6500 in two healthy individuals, was found on the Martin Probst syndrome gene (RAB40AL). Based on XCI studies on the patient's mother, it is likely that RAB40AL escapes XCI, while still remaining balanced. In conclusion, the results of the present study indicated that the Martin Probst syndrome is an X‑linked condition, which is probably not caused by RAB40AL mutations. Although NGS is a powerful tool to identify pathogenic mutations, the analysis of genetic data requires expert critical revision of all detected variants.

Block of the mevalonate pathway triggers oxidative and inflammatory molecular mechanisms modulated by exogenous isoprenoid compounds. - Tricarico, Paola Maura; Kleiner, Giulio; Valencic, Erica; Campisciano, Giuseppina; Girardelli, Martina; Crovella, Sergio; Knowles, Alessandra; Marcuzzi, Annalisa (Int J Mol Sci, 2014)
Deregulation of the mevalonate pathway is known to be involved in a number of diseases that exhibit a systemic inflammatory phenotype and often neurological involvements, as seen in patients suffering from a rare disease called mevalonate kinase deficiency (MKD). One of the molecular mechanisms underlying this pathology could depend on the shortage of isoprenoid compounds and the subsequent mitochondrial damage, leading to oxidative stress and pro-inflammatory cytokines' release. Moreover, it has been demonstrated that cellular death results from the balance between apoptosis and pyroptosis, both driven by mitochondrial damage and the molecular platform inflammasome. In order to rescue the deregulated pathway and decrease inflammatory markers, exogenous isoprenoid compounds were administered to a biochemical model of MKD obtained treating a murine monocytic cell line with a compound able to block the mevalonate pathway, plus an inflammatory stimulus. Our results show that isoprenoids acted in different ways, mainly increasing the expression of the evaluated markers [apoptosis, mitochondrial dysfunction, nucleotide-binding oligomerization-domain protein-like receptors 3 (NALP3), cytokines and nitric oxide (NO)]. Our findings confirm the hypothesis that inflammation is triggered, at least partially, by the shortage of isoprenoids. Moreover, although further studies are necessary, the achieved results suggest a possible role for exogenous isoprenoids in the treatment of MKD.
Keywords: Animals; Apoptosis; Carotenoids; Carrier Proteins; Cell Line; Cytokines; Diterpenes; Humans; Mevalonate Kinase Deficiency; Mevalonic Acid; Mice; Mitochondria; Nitric Oxide; Phytol; Terpenes

Breastfeeding to 24 months of age in the northeast of Italy: a cohort study. - Carletti, Claudia; Pani, Paola; Knowles, Alessandra; Monasta, Lorenzo; Montico, Marcella; Cattaneo, Adriano (Breastfeed Med, 2011)
AIM: This study assessed the prevalence and duration of breastfeeding up to 24 months and the associated socioeconomic determinants in a birth cohort of children. METHODS: Four hundred infants born in a hospital in the north east of Italy were enrolled at birth and followed up for 36 months. Data on infant feeding were gathered through a feeding diary compiled at fixed intervals. Data were also gathered on type of delivery and weight, length, and health status at birth, as well as on selected socioeconomic indicators of the mothers. A multivariate logistic regression analysis was used to determine any association that exclusivity and duration of breastfeeding may have with selected socioeconomic variables and with health conditions of the infants at birth. RESULTS: Ninety-eight percent of mothers initiated breastfeeding, 69% of them exclusively. This rate, however, had declined to 6% by 6 months. There was a remarkable endurance of breastfeeding at 24 months (12%). The variables significantly associated with exclusive breastfeeding at 3 months and any form of breastfeeding at 12 months are mother's age (p=0.007 at 3 months, p=0.026 at 12 months) and postdischarge hospital admission (p=0.029 at 3 months). CONCLUSIONS: In this population, breastfeeding rates are higher than previously reported, but lower than recommended, especially as far as exclusivity is concerned. Full implementation of the World Health Organization-UNICEF Baby Friendly Initiatives in hospitals and communities is needed to improve them further. Monitoring systems should include the collection of data on breastfeeding beyond 12 months of age.
Keywords: Adult; Age Factors; Birth Weight; Breast Feeding; Cohort Studies; Family Characteristics; Female; Gestational Age; Guideline Adherence; Health Promotion; Humans; Infant; Infant, Newborn; Italy; Neonatal Screening; Prevalence; Socioeconomic Factors; Time Factors